Análisis Espaciotemporal y Cinemático de la Marcha en Pacientes con Parálisis Cerebral Espástica - Ruiz Padilla, Paola Elizabeth; Lora Castro, Sorpresa; Alvarado Rodriguez, Francisco Javier; Perez Moreno, Juan Carlos; Velez Perez, Hugo Abraham (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
The spatio-temporal and kinematic data analysis of gait in patients with cerebral palsy is important to understand the alterations in their gait cycle allowing correct diagnoses, plan surgeries or establish effective rehabilitation therapies. However, access to the records acquired by commercial equipment is limited given the acquisition, storage and format protocols that each commercial brand establishes for its equipment. Biomark is a useful computational tool previously developed in our work team and used in this study to extract, convert, analyze and process recordings from a commercial device for gait analysis. The recordings were acquired in the Gait Analysis Laboratory of the Centro de RehabilitaciónInfantilTeletón (CRIT) de Occidente and correspond to 19 children aged 6.4 years old on average and diagnosed with Gross Motor Paraparesis II-III. The spatio-temporal parameters and kinematic descriptors were calculated using the Biomark Toolbox. The results demonstrated that Biomark is auseful auxiliary computational tool for the calculation and analysis of gait parameters. In general terms, it was observed that the gait pattern in patients with cerebral palsy is crouched, with greater hip, knee and dorsal ankle flexion at initial contact, showing a higher percentage of stance and decreased swing phase with respect to nominal values. The decreased speed, stride length and cadence are derived from muscular dystrophy. Future work suggests the implementation of an electronic medical file for the quantitative follow-up of the parameters of the patients’ gait, allowing an early evaluation and adjustment of rehabilitation strategies.